2016
DOI: 10.1002/anie.201511792
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hybrid Perovskite Tin Iodide Single Crystals by Top‐Seeded Solution Growth

Abstract: Hybrid perovskites have generated a great deal of interest because of their potential in photovoltaic applications. However, the toxicity of lead means that there is interest in finding a nontoxic substitute. Bulk single crystals of both cubic CH3NH3 SnI3 and CH(NH2)2 SnI3 were obtained by using the top-seeded solution growth method under an ambient atmosphere. Structural refinement, band gap, thermal properties, and XPS measurements of CH3NH3 SnI3 and CH(NH2)2 SnI3 single crystals are also reported in detail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
239
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(258 citation statements)
references
References 17 publications
19
239
0
Order By: Relevance
“…The use of lead-containing substances in electronic devices is severely restricted by the European Union and other countries, motivating the development of lead-free PSCs. [16] The aforementioned considerations provide the rationale for the investigation of CsSnI 3 material as a promising thermally stable, lead-free perovskite for next generation PSCs. Second, it has been suggested that the fragmentation of the organic component (e.g., MA + or FA + ) in those hybrid perovskites may make them intrinsically unstable for long-term outdoor applications of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The use of lead-containing substances in electronic devices is severely restricted by the European Union and other countries, motivating the development of lead-free PSCs. [16] The aforementioned considerations provide the rationale for the investigation of CsSnI 3 material as a promising thermally stable, lead-free perovskite for next generation PSCs. Second, it has been suggested that the fragmentation of the organic component (e.g., MA + or FA + ) in those hybrid perovskites may make them intrinsically unstable for long-term outdoor applications of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[16,23] Some have reported more stable devices employing [(NH 2 ) 2 CH]SnI 3 (FASnI 3 ), which presumably results from the enhanced interaction between Sn 2+ and larger sized FA + , making FASnI 3 an attractive candidate. [19,20,24] Mesoporous titanium dioxide (TiO 2 ) scaffold layers have been used to demonstrate Sn-based perovskite solar cells. [13][14][15][16][17]19,20] However, high-temperature (>450 °C) is required for preparing mesoporous TiO 2 scaffold structure.…”
mentioning
confidence: 99%
“…[19,20,24] Mesoporous titanium dioxide (TiO 2 ) scaffold layers have been used to demonstrate Sn-based perovskite solar cells. [19,20,24] Mesoporous titanium dioxide (TiO 2 ) scaffold layers have been used to demonstrate Sn-based perovskite solar cells.…”
mentioning
confidence: 99%
“…1b) that is common for general MAPbI 3 /MASnI 3 perovskite crystals. 26,28 More pictures of the MASnI 3 wafers are provided in Fig. S1.…”
mentioning
confidence: 99%
“…The MASnI 3 shows strong absorption across the entire visible spectrum and therefore it is seen as black in color. The band gap value was estimated on the basis of the Tauc plot as the intercept value of the plot of (ahn) 1 28 The obtained MASnI 3 exhibits PL peak at 930 nm as shown in Fig. 5b.…”
mentioning
confidence: 99%